Gendered lives, constrained choice and young African women's PrEP uptake and persistent use as a gender-responsive approach to HIV prevention - Rousseau, Elzette (Department of Medicine, 2025)
While there is substantial momentum to scale up PrEP (pre-exposure prophylaxis) for HIV prevention in adolescent girls and young women (AGYW), this population is demonstrating difficulty in sustained PrEP use. PrEP use at the time of HIV exposure is critical for effectiveness. This thesis investigated AGYW's decision-making throughout the PrEP-user journey (from PrEP uptake to persistence or discontinuation). It reflected on the role of agency (personal and relational), gender, and PrEP access and how these facilitated or constrained PrEP use. The research used a multi-method approach, including pharmacy record review, in-depth interviews, and structured surveys. This cohort included 2550 AGYW participants (aged 16-25 years) of the POWER implementation study receiving oral PrEP for up to 36 months in Cape Town and Johannesburg, South Africa, and Kisumu, Kenya. The POWER study was designed to develop and evaluate scalable models of PrEP delivery. Across analyses, PrEP uptake facilitators included PrEP integration with sexual and reproductive health services but were hampered by PrEP misconceptions and stigma in the community. Disclosure, social support, adolescent-friendly counselling, and convenient access were key enablers for PrEP persistence. Beyond this, AGYW were influenced by intrinsic (strong self-determination and autonomy finding PrEP adherence personally fulfilling) and extrinsic motivations (where PrEP use habits are influenced by external factors or rewards, social pressure, or fear of negative relational consequences). The research showed that AGYW's diversity in needs, habits, and lifestyles also influenced their PrEP access preferences, which led to the segmentation of this group into convenient, independent, social, or discreet PrEP users for optimised tailored service delivery. While the role of sexual relationship power in AGYW's PrEP continuation was also investigated, no significant influence was observed. In conclusion, the findings suggest that AGYW are empowered to make positive PrEP use decisions when their agency is ignited and/or when AGYW are presented with access alternatives to choose from (differentiated models of PrEP delivery). AGYW's agency fluctuated in contexts of community stigma, non-disclosure, harmful relationship dynamics, and emotional arousal; however, differentiated PrEP access created alternatives (a potential buffer zone) for these instances of limited agency.